2023
DOI: 10.1210/endrev/bnad003
|View full text |Cite
|
Sign up to set email alerts
|

LGR4: A New Receptor Member in Endocrine and Metabolic Diseases

Abstract: Classic hormone membrane receptors, such as leucine-rich repeat-containing G protein-coupled receptor (LGR) 1 (follicle-stimulating hormone receptor/FSHR), LGR2 (luteinizing hormone receptor/LHR), and LGR3 (thyrotropin receptor/TSHR), are crucial in endocrinology and metabolism, and the identification of new receptors can advance this field. LGR4 is a new member of this G protein-coupled receptor family and shows expression and function ways similar to those of LGR1/2/3. Several recent studies have reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 227 publications
1
4
0
Order By: Relevance
“… 15 Changes in its activity have been linked to obesity and other metabolic diseases. 16 , 17 Recently, we found that Ctnnb1 deficiency in mature adipocytes could resist high-fat diet-induced obesity without affecting adipocyte identity, which was consistent with recent findings from the MacDougald group. 18 , 19 Canonical WNT pathway agonists could inhibit the expression of Ucp1 in mature brown adipocytes without affecting other differentiation-related genes, such as Ppar γ , C/ebpα , and Fabp4 , 20 while it is noteworthy that Adiponectin -cre-driven Ctnnb1 knockout in BAT has no impact on the expression of Ucp1 , 19 which is the key effector of adaptive thermogenesis.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“… 15 Changes in its activity have been linked to obesity and other metabolic diseases. 16 , 17 Recently, we found that Ctnnb1 deficiency in mature adipocytes could resist high-fat diet-induced obesity without affecting adipocyte identity, which was consistent with recent findings from the MacDougald group. 18 , 19 Canonical WNT pathway agonists could inhibit the expression of Ucp1 in mature brown adipocytes without affecting other differentiation-related genes, such as Ppar γ , C/ebpα , and Fabp4 , 20 while it is noteworthy that Adiponectin -cre-driven Ctnnb1 knockout in BAT has no impact on the expression of Ucp1 , 19 which is the key effector of adaptive thermogenesis.…”
Section: Introductionsupporting
confidence: 91%
“…The canonical WNT pathway has been shown to influence adipogenesis, obesity, and fat distribution. 16 , 17 A substantial body of literature has focused on the inhibitory effects of canonical WNT signaling during the early stages of adipogenesis. 38 , 39 , 40 In our recent study, we discovered that β-catenin in mature adipocytes exacerbated adipose tissue expansion by regulating the crosstalk among mature adipocytes, macrophages, and preadipocytes during the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream signaling mediated by LGR4 primarily includes cAMP/PKA, Wnt/β-catenin, Gαq/GSK3β and Gαq/ PKCα signaling pathways. In addition, LGR4 can regulate AKT, extracellular signal-regulated kinase (ERK), and nuclear factor kappa-B (NF-κB) pathways 26 . However, how these signaling pathways regulate intestine epithelium remains unclear, and needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance in bone tissue hampers glucose uptake and increases blood glucose levels, thereby impairing Runx2 activity and osteogenic differentiation. In addition, reduced glucose uptake diminishes acetyl-CoA levels and the TCA cycle, which play crucial roles in the posttranslational acetylation and transcriptional activity of osterix and Runx2 43 . Importantly, disrupted glucose metabolism caused by insulin resistance reduces the energy available for physiological processes such as osteoblast differentiation, bone-related protein secretion, and biomineralization.…”
Section: Microenvironmental Hallmarks Of Osteoporosismentioning
confidence: 99%